Mangrove Plant Community Structure of Kwala Indah Village, Batu Bara Regency - Purba, Ricky Tommy Fransiskus; Barat, Welmar Olfan Basten; Siburian, Daniel Tony E (Journal of Applied Geospatial Information, 2023)
Coastal areas are transitional areas between land and marine ecosystems that have high biological productivity. Mangroves are a type of plant that grows in coastal areas or river estuaries and has an ecological function by acting as the last defense against sea waves after coral reef and seagrass ecosystems, as sediment traps, as a place to find fish food, as a fish spawning ground, as a shelter, and as a place for fish farming. Mangrove Plant Community Structure Research in the Kwala Indah Village Area was conducted in August–October 2023 with the aim of knowing the types of mangroves, mangrove diversity and uniformity, dominance, Important Value Index (INP), and mangrove crown cover in Kwala Indah Village. The method used in the observation of mangrove plant community structure is to use the quadrant transect method by analyzing species density, relative density, species frequency, relative frequency, species dominance, relative dominance, and important value index at the tree, sapling, and seedling levels, as well as crown cover. Based on the results of the study, 7 species were found, namely Xylocarpus granatum, Xylocarpus mekongensis, Rhizophora apiculata, Rhizophora mucronata, Soneratia alba, Bruguiera parviflora, and Excoecaria agallocha. Xylocarpus and Rhizopora have the highest INP, diversity, uniformity, and dominance. Canopy cover is in the medium category; coastal areas are transitional areas between terrestrial and marine ecosystems that have high biodiversity values.